Banking on Snow: Bank Capital, Risk, and Employment - Simon Baumgartner; Alex Stomper; Thomas Schober; Rudolf Winter-Ebmer (Institute of Labor Economics (IZA), 2022)
How does small-firm employment respond to exogenous labor productivity risk? We find that this depends on the capitalization of firms' local banks. The evidence comes from firms offering (quasi-) fixed employment to workers whose productivity depends on the weather. Weather risk reduces this employment, and the effect is stronger in regions where the regional banks have less equity capital. Bank capitalization also proxies for the extent to which the regional banks' borrowers can obtain liquidity when the regions are hit by weather shocks. We argue that, as liquidity providers, well-capitalized banks support economic adaptation to climate change.
Keywords: J23; J41; E44; 330; quasi-fixed employment; labor productivity risk; bank liquidity